Bioactive fraction of Rhodiola algida against chronic hypoxia-induced pulmonary arterial hypertension and its anti-proliferation mechanism in rats. (24th April 2018) - Nan, Xingmei; Su, Shanshan; Ma, Ke; Ma, Xiaodong; Wang, Ximeng; Zhaxi, Dongzhu; Ge, Rili; Li, Zhanqiang; Lu, Dianxiang
Abstract: Ethnopharmacological relevance: Rhodiola algida var. tangutica (Maxim.) S.H. Fu is a perennial plant of the Crassulaceae family that grows in the mountainous regions of Asia. The rhizome and roots of this plant have been long used as Tibetan folk medicine for preventing high latitude sickness. Aim of the study: The aim of this study was to determine the effect of bioactive fraction from R. algida (ACRT) on chronic hypoxia-induced pulmonary arterial hypertension (HPAH) and to understand the possible mechanism of its pharmacodynamic actions. Materials and methods: Male Sprague-Dawley rats were separated into five groups: control group, hypoxia group, and hypoxia+ACRT groups (62.5, 125, and 250 mg/kg/day of ACRT). The chronic hypoxic environment was created in a hypobaric chamber by adjusting the inner pressure and oxygen content for 4 weeks. After 4 weeks, major physiological parameters of pulmonary arterial hypertension such as mPAP, right ventricle index (RV/LV+S, RVHI), hematocrit (Hct) levels and the medial vessel thickness (wt%) were measured. Protein and mRNA expression levels of proliferating cell nuclear antigen (PCNA), cyclin D1, p27Kip1 and cyclin-dependent kinase 4 (CDK4)) were detected by western blotting and real time PCR respectively. Chemical profile of ACRT was revealed by ultra performance liquid chromatography coupled with quadrupole time of flight mass spectrometry (UHPLC-Q-TOF-MS/MS). Results: The results showed that a successful HPAH rat model was established in a hypobaric chamber for 4 weeks, as indicated by the significant increase in mPAP, RV/LV+S, RV/BW and wt%. Compared with the normal group, administration of ACRT reduced mPAP, right ventricular hypertrophy, pulmonary small artery wall thickness, and damage in ultrastructure induced by hypoxia in rats. PCNA, cyclin D1, and CDK4 expression was reduced ( p <0.05), and p27Kip1 expression increased ( p <0.05) in hypoxia+ACRT groups compared to hypoxia. 38 constituents in bioactive fraction were identified by UHPLC-Q-TOF-MS/MS. Conclusion: Our results suggest that ACRT could alleviate chronic hypoxia-induced pulmonary arterial hypertension. And its anti-proliferation mechanism in rats based on decreasing PCNA, cyclin D1, CDK4 expression level and inhibiting p27Kip1 degradation. Graphical abstract: